SISTEM INFORMASI ABSENSI SISWA PADA SMK NEGERI 1 PANTAI LABU BERBASIS WEB DENGAN WHATSAPP GATEWAY - Paiman Nababan; Jamaluddin Jamaluddin; Resianta Perangin-angin; Eviyanti N. Purba (Universitas Methodist Indonesia, 2022)
State Vocational High School 1 Pantai Labu is a vocational school located on Jl.Pasar XII Desa Durian. The student attendance system still uses it manually in the form of sheets of paper. Student absenteeism often occurs in one room, so it is difficult for schools and parents to submit reports on their children's attendance. Because parents understand their children's attendance reports when taking report cards, so there are some students who skip school. This problem is certainly troublesome for schools and parents. based on the problem, of course for parents that their children are in school, want to monitor their children who are participating in learning activities. Observing the above problems, it is necessary to have a web-based student attendance system with whatsapp gateway. The waterfall method is divided into several terms, namely planning, analysis, design and implementation. Data collection will use literature review, field review and interview methods. PHP, HTML, CSS and Javascript programming languages. The author will build a Web-Based Student Attendance Information System using the Whatsapp Gateway. In the system, it has been used as student attendance at school while controlling the level of student attendance at school in real time by sending WhatsApp messages. So that it is understandable for schools as well as for parents. Keywords: Information System, Attendance Information System, Whatsapp